Architecture of the bronchial tree in Cuvier's dwarf caiman (Paleosuchus palpebrosus). Issue 10 (4th April 2022) - Schachner, Emma R.; Diaz, Raul E.; Coke, Rob; Echols, Scott; Osborn, Michelle L.; Hedrick, Brandon P.
Abstract: We imaged the lungs of five Cuvier's dwarf caiman ( Paleosuchus palpebrosus ) via computed tomography (CT) and micro‐computed tomography (μCT) and compared these data to the lungs of the American alligator ( Alligator mississippiensis ). These data demonstrate anatomical commonalities between the lungs of P. palpebrosus and A. mississippiensis, and a few notable differences. The structural similarities are (a) a proximally narrow, distally widened, hook‐shaped primary bronchus; (b) a cervical ventral bronchus that branches of the primary bronchus and immediately makes a hairpin turn toward the apex of the lung; (c) a sequential series of dorsobronchi arising from the primary bronchus caudal to the cervical ventral bronchus; (d) intraspecifically highly variable medial sequence of secondary airways; (e) sac‐like laterobronchi; and (f) grossly dead‐ended caudal group bronchi in the caudal and ventral aspects of the lung. The primary differences between the two taxa are in the overall number of large bronchi (fewer in P. palpebrosus ), and the number of branches that contribute to the cardiac regions. Imaging data of both a live and deceased specimen under varying states (postprandial, fasting, total lung capacity, open to atmosphere) indicate that the caudal margin and position of the lungs shift craniocaudally relative to the vertebral column. These imaging data suggest that the smooth thoracic ceiling may be correlated to visceral movement during ventilation, but this hypothesis warrants validation. These results provide the scaffolding for future comparisons between crocodilians, for generating preliminary reconstructions of the ancestral crocodilian bronchial tree, and establishing new hypotheses of bronchial homology across Archosauria.